Cocaine self-administration in social dyads using custom-built operant conditioning chambers - Lacy, Ryan T.; Strickland, Justin C.; Smith, Mark A. (Journal of neuroscience methods, 2014)
•We used custom-built chambers to assess social cocaine self-administration.•Dyads exhibited reliable responding on fixed interval schedules with a limited hold.•Dyadic responding became more similar across testing days.•We characterized a preclinical model of social drug taking behavior in dyads. Traditionally, the analysis of intravenous drug self-administration is limited to conditions in which subjects are tested in isolation. This limits the translational appeal of these studies because drug use in humans often occurs in the presence of others. We used custom-built operant conditioning chambers that allowed social dyads visual, olfactory, auditory, and limited tactile contact while concurrently self-administering cocaine. Male rats were trained to respond according to a fixed interval schedule of reinforcement (with a limited hold) in order to determine if patterns of cocaine (0.75mg/kg/infusion) self-administration became more similar over time in social pairs. Cocaine self-administration was tested across five days according to a 10-min fixed interval schedule (with a 5-min limited hold). Quarter-life values (time at which 25% of responses were emitted per interval) were analyzed using intraclass correlations. The total number of reinforcers obtained did not vary across the five days of testing; however, quarter-life values became progressively more similar between individuals within the social dyads. Standard operant conditioning chambers are unable to assess responding in multiple animals due to their small size, the need to prevent subjects from responding on the lever of their partner, and the need to prevent infusion lines from entangling. By using custom-built social operant conditioning chambers, we assessed the effects of social contact on cocaine self-administration. Social operant conditioning chambers can be used as a preclinical method to examine social influences on drug self-administration under conditions that approximate human substance use.